Pathways of the sacred - Negrão, Lísias Nogueira (Tempo Social, 2008)
The aim of this article is to analyze the current dynamic of the São Paulo religious field, seen not through the plurality of its religious organizations, nor through the positions adopted by ecclesiastical or group leaders. Instead, I focus on the individual religious agents and their attitudes in response to a growing religious pluralism and diversification. The work therefore looks at individuals who are 'religious mutants:' people who have changed their religious affiliation at least once during their lives, or who are religious duplicates or multiplicates, participants of two or more symbolic-religious universes simultaneously. By studying people's religious trajectories, we can analyze their beliefs and religious practices irrespective of their affiliation to specific organized groups. With the single exception of the Protestants, still anchored in the conception of a transcendent God and a strong ecclesiality (though the Pentecostals diverge slightly through their incorporation of magic), we can perceive a trend towards a kind of religiosity that Troeltsch called mystic - and which Campbell identifies as its orientalization. The followers of other religions, or the duplicates/multiplicates, tend towards mystical religious ideas and magical practices lived out in private, accept frequenting a variety of religious groups and repudiate clerical authoritarianism. The old conflicts of traditional religious duplicities (Catholicism/Spiritism; Catholicism/Afro-Brazilian Religions) have been amplified with new forms (Catholic/Protestant; Catholic/Other Religions) and with the emergence of multiplicity, reproducing in Brazilian style the same transformations experienced throughout the West for a long time.